Small Hydropower Plant for Sustainable Electricity from RES Mix - Bogdan Popa (MDPI AG, 2021)
In the context of the need for an increasing share of renewables in electricity mixes, the paper presents the existing RES mix, PV and wind, for partially covering the electricity consumption of a research institute, ICSTM, and proposes a solution for completion with a third form of RES, a small hydropower plant. Moreover, it is envisaged to include the proposed small hydropower plant as a new real-scale laboratory attached to ICSTM. The method includes the presentation of an existing proposal for increasing installed capacity in new PV panels and propose to install an SHPP to a weir situated a few hundred meters from the institute. The hydropower potential for two possible arrangements is assessed and some types of turbines suitable for this location are presented. The main results demonstrate that building an SHPP is a better solution for completion of PV and wind as source of electricity for ICSTM. The main conclusion of the paper is that by installing new RES capacities, ICSTM can build a real-scale laboratory for new technologies, at the same time fully covering its own electricity consumption and even supplying a green electricity mix into the national power system.